(untitled) (Nordic Journal of Practical Theology, 2022)
The article presents results from a study of drop-in baptisms in Norway. The study is based on interviews with parents who have chosen to baptise their children by drop- in baptism and with adults who have been baptised. They were baptised in different congregations in the Church of Norway from 2015 to 2019. The article tries to answer two questions: what were their reasons for being baptised, and why did they choose drop-in baptism? The study shows that the baptism functions as an initiation ritual into different communities, which gave a feeling of belonging and identity. It also shows that authenticity is important for people to explain their reason for baptism, and that drop-in baptism fits well into the life of the modern person. The study uncovers the diversity and complexity of the religiosity and shows the different motives humans have for choosing drop-in baptism. This study will contribute to a better understanding of what people are thinking about baptism and to the discussion about further practices in the church.